2013
DOI: 10.1097/igc.0b013e318292da82
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of Nuclear Factor κB Contributes to Cystic Fibrosis Transmembrane Conductance Regulator Expression and Promotes Human Cervical Cancer Progression and Poor Prognosis

Abstract: Cystic fibrosis transmembrane conductance regulator and NF-κB were coexpressed in cervical cancer, and the activation of NF-κB mediated the expression of CFTR. Multivariate analysis revealed that coexpression of CFTR and NF-κB was associated with poor prognosis in patients with cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…Since several groups have shown that E1s of various papillomaviruses induce activation of DDR (11-13), we believe that a negative feedback loop between E1 and NF-B might constitute a common mechanism to regulate E1 levels in the basal compartment of the infected tissue. Interestingly, it has been reported that NF-B is upregulated in basal cells of a fraction of CIN1 compared with normal tissues (22). The reported percent NF-B positivity in low-grade cervical lesions has varied from study to study; some authors have indicated that upregulation of NF-B is detected only in cervical cancer while others indicated that it is already present in the basal compartment in 30% of CIN1 lesions (17,19).…”
Section: Activation Of Nf-b By E1 Through Ddrmentioning
confidence: 91%
See 1 more Smart Citation
“…Since several groups have shown that E1s of various papillomaviruses induce activation of DDR (11-13), we believe that a negative feedback loop between E1 and NF-B might constitute a common mechanism to regulate E1 levels in the basal compartment of the infected tissue. Interestingly, it has been reported that NF-B is upregulated in basal cells of a fraction of CIN1 compared with normal tissues (22). The reported percent NF-B positivity in low-grade cervical lesions has varied from study to study; some authors have indicated that upregulation of NF-B is detected only in cervical cancer while others indicated that it is already present in the basal compartment in 30% of CIN1 lesions (17,19).…”
Section: Activation Of Nf-b By E1 Through Ddrmentioning
confidence: 91%
“…Increased expression of NF-B has been described for HPVassociated lesions such as cervical cancers as well as their precursor lesions and laryngeal papillomas and cancers (17)(18)(19)(20)(21)(22). Several studies have shown that E6 and E7 proteins of HPVs modulate NF-B pathways (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…When the CFTR is functional, it is possible ion transportation activities do not account for the main aspect of the tumorigenesis. CFTR has also recently been related to cervical cancer [61][62][63] . A series of studies from Peng et al [61] demonstrated that the expression of CFTR is gradually increased from normal to pre-cancerous cervical tissue and cervical cancer tissues, and it is also positively correlated to histological grades, tumor stage, and metastatic grades.…”
Section: Cftr and Other Cancersmentioning
confidence: 99%
“…A series of studies from Peng et al [61] demonstrated that the expression of CFTR is gradually increased from normal to pre-cancerous cervical tissue and cervical cancer tissues, and it is also positively correlated to histological grades, tumor stage, and metastatic grades. In addition, further investigation by the Peng et al [61] indicated that the upregulated CFTR in pre-cancerous and cervical cancer tissues resulted from aberrantly increased NF-kB p65 translocation [62] . RNA sequencing results obtained from samples co-existing with pre-cancerous lesions and adjacent normal cervical tissue demonstrated that CFTR was also significantly up-regulated in cervical cancer [63] , which is in agreement with the findings from Peng et al [61] and Wu et al [62] .…”
Section: Cftr and Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation